Determinants of Intention to Uptake COVID-19 Vaccination Among Saudi Adults: Application of the Health Belief Model - Alshagrawi SS (Dove Medical Press, 2024)
Salah S Alshagrawi Saudi Electronic University, College of Health Sciences, Department of Public Health, Riyadh, Saudi ArabiaCorrespondence: Salah S Alshagrawi, Email s.alshagrawi@seu.edu.saIntroduction: The pandemic caused by COVID-19 has had a profound effect on global health. Due to its potential impact on the efficacy of pandemic control measures, vaccine hesitancy (VH) in relation to COVID-19 has emerged as a significant concern. The attainment of herd immunity is contingent on the rate of COVID-19 vaccine adoption. Despite this, there have been reports of reluctance toward the COVID-19 vaccine. This study seeks to investigate the effect of constructs that influence adults' intentions to receive COVID-19 vaccination using the Health Belief Model (HBM).Methods: A cross-sectional study was conducted by recruiting Saudi Arabian adults as participants. Using Structural Equation Modeling (SEM), the proposed HBM model was evaluated. A total of 505 individuals replied to the survey.Results: The suggested HBM model explained 68% of the variation in intention to get COVID-19 immunization. I found all HBM variables namely perceived susceptibility, greater levels of perceived behavioral control, severity, benefits, and barriers to be significant predictors of vaccination intentions. Among demographic variables, only married status had a significant relationship with the intention to obtain COVID-19 immunization.Discussion: The findings of this study indicate that the HBM can be utilized effectively to obtain insight into the factors that influence COVID-19 prevention measure adherence. Understanding and recognizing individuals' perceived health beliefs and practices is essential for the development of effective COVID-19 intervention strategies.Keywords: immunization, COVID-19, health belief model, vaccine hesitancy, structural equation modeling, Saudi Arabia